Performing Problems on the Pavement: An Innovative Approach to Architectural Education in Post-Apartheid South Africa. Issue 2 (2nd July 2016) - Horner, Bridget; Young-Jahangeer, Miranda; Dhunpath, Rubby
Abstract : In this article we interrogate the possibility and benefits of introducing alternative participatory pedagogies to architecture students at the University of KwaZulu-Natal, in order to mediate the gap between students' knowledge of the living environments they are expected to design and the authentic, lived realities of the inhabitants of those environments. Architecture students, assisted by applied theater students, devised participatory theater on the pavement of downtown Durban. 1 This approach encouraged in situ engagement between students and the typically marginalized inhabitants of that area. Moreover, these participatory performances served as a catalyst to disrupt some commonly held perceptions around the notion of "the expert" and provoked a possible reimagining of an architectural pedagogy that was responsive to the South African context.